2018
DOI: 10.1016/j.athoracsur.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Muscle Size Predicts Risk-Adjusted Outcomes After Surgical Aortic Valve Replacement

Abstract: Psoas index is an easily obtained and reproducible measure of frailty that predicts risk-adjusted resource utilization, morbidity, and long-term mortality. Psoas index may improve procedural selection and risk adjustment in high-risk patients with aortic valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 34 publications
2
84
0
3
Order By: Relevance
“…The characteristic of PMI as a reflection of the skeletal muscle condition of the whole body may need further discussion. Indeed PMI was reported to be an effective predictor of major postoperative complications in many clinical studies [57][58][59] and our meta-analysis has also validated this role.…”
Section: Discussionsupporting
confidence: 71%
“…The characteristic of PMI as a reflection of the skeletal muscle condition of the whole body may need further discussion. Indeed PMI was reported to be an effective predictor of major postoperative complications in many clinical studies [57][58][59] and our meta-analysis has also validated this role.…”
Section: Discussionsupporting
confidence: 71%
“…They found that the measurement of psoas muscle area is more predictive for mortality than other clinical parameters. Hawkins et al [31] determined the place of psoas muscle size as a finding of frailty for the prediction of risk-adjusted outcomes in moderate to high-risk patients after aortic valve placement. They calculated the psoas index by dividing the mean psoas cross-sectional area to the body surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Several recently published articles measuring muscle mass for diagnosis of sarcopenia, however, have evaluated the psoas muscle. [2][3][4] This suggests that measurement of regional muscle mass, such as the area or volume of the psoas muscle, can be performed easily in clinical practice at many centers.…”
Section: Sarcopenia Andmentioning
confidence: 99%